2010
DOI: 10.1111/j.1469-0691.2009.02826.x
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 DNA proviral load in treated and untreated HIV-1 sero-positive patients

Abstract: As proviral human immunodeficiency virus type 1 (HIV-1) DNA can replenish and revive viral infection upon activation, its detection might offer significant therapeutic information, complementing the input provided by plasma RNA determination in the follow-up of infected individuals. A selected group of acutely infected subjects was studied to verify both total and 2-long terminal repeat (2-LTR) DNA proviral load during the acute phase of infection and thereafter. Patients were divided in two sex- and age-match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…4B). This is consistent with the observation that cART-treated individuals show a significant decrease in total HIV DNA proviral load in peripheral blood mononuclear cells (PBMCs) (34). The lack of suppression in the brain is probably due to less penetration of the drugs (Fig.…”
Section: Resultssupporting
confidence: 90%
“…4B). This is consistent with the observation that cART-treated individuals show a significant decrease in total HIV DNA proviral load in peripheral blood mononuclear cells (PBMCs) (34). The lack of suppression in the brain is probably due to less penetration of the drugs (Fig.…”
Section: Resultssupporting
confidence: 90%
“…Houzet et al had observed similar overlap in their comparison of naive PBMC/HIV-1 NL4-3 and uninfected activated T cells [55]. We consider the 50% overlap between CEMx174/HIV-1 NL4-3 and patient samples to be appreciable given the differences in cell lineage, infection parameters and the admixture of uninfected cells in blood samples from patients [63]. We speculate that the overlap identified with patient PBMCs, despite the admixture with uninfected cells, is attributable to paracrine signaling or another bystander effect that is not solely seen by T cell activation.…”
Section: Resultsmentioning
confidence: 90%
“…Infection through CCR5 frequently generated viral-induced MGC, while coreceptor-negative NP-2/CD4 cells did not form any cluster of nuclei (data not shown). Typically when cells become infected by HIV and SIV, viral DNA provirus forms by reverse transcription of genomic RNA into double stranded DNA followed by subsequent integration into host DNA [32]. We further demonstrated infection through the CKR-L3 and CCR6 coreceptors through the detection of proviral DNA in infected cell lines (Figure 3b).…”
Section: Resultsmentioning
confidence: 60%